Impact of Social Work Services on the Resilience of Migrant Children. (March 2022) - Huang, Dan; Lin, Wenyi; Luo, Yingting; Liu, Yang
Purpose: This study examines the effectiveness of social work services designed to enhance resilience among migrant children in urban China. Methods: We selected four primary schools (i.e., two public and two private migrant schools) in the X District, Guangzhou City, China. A total of 461 valid samples were surveyed for analysis. Three regression models were employed to explain the influence of social work services on students' resilience. Results: Social work services exert a positive and significant influence on the resilience of migrant children. Concretely, social work services in terms of educational activities, interest activities, and psychological counseling affected the resilience of migrant children after controlling for the impact of social capital, self-efficacy, and individual and household economic status. Moreover, students who participated in educational activities exhibit superior resilience. Discussion: Social work organizations should provide more participation opportunities and diversified service items to migrant children.